Adherencia al tratamiento antihipertensivo y su relación con la funcionalidad familiar en adultos medios. Parroquia La Avanzada. Año 2016. - Sánchez Sandoval, Damarys Katherine (2017)
Hypertension (AH) is a disease with a high prevalence worldwide, and is defined as uncontrolled at rates greater than 140/90 ml / Hg. Due to the increased risk of complications due to non-adherence to medication, we believe it is associated with poor family functionality, we have found it necessary to study this association. The objective of this study is to evaluate the relationship between adherence to antihypertensive treatment and family function in hypertensive patients aged 35-64 years. The study is descriptive, analytical, correlational; With non-experimental quantitative approach, and cross-sectional causality design. It was carried out in the La Avanzada parish of Santa Rosa, in the first half of 2016. We studied 130 patients diagnosed with hypertension in the Health Sub-center of the Ministry of Public Health. A field data collection questionnaire, the FFSIL test and the Morisky - Green Levine test were used for the measurements. The variables to be evaluated were: age, sex, marital status, economic activity, socioeconomic condition, family functionality, adherence to treatment and control of blood pressure. The data and variables were processed using the statistical software SPSS (Statistical Package for the Social Sciences) version 16. The results obtained a greater number of non-adherent antihypertensive patients (34.88%), as well as the They do not work (27.78%). People with regular socioeconomic status (29.58) and poor (29.03%) have a higher prevalence of non-adherence to antihypertensive treatment. These patients who did not adhere to the treatment resulted in uncontrolled systolic (63.33%) and diastolic (21.28%) blood pressure, higher than 140 and 90 respectively. And of these patients the functional families have higher prevalence (27.12%). In conclusion, family functionality does not improve adherence to antihypertensive treatment in middle-aged adults. KEY WORDS: arterial hypertension, family, chronic patients, therapeutic compliance, rural environment.